Presejanje na spolno prenosljivo klamidijsko okužbo - pregled priporočil - Grgič-Vitek, Marta (Zdravstveno varstvo, 2008)
Aim: Numerous complications of untreated sexually transmitted clamydial infection contribute to its public health importance. The burden of sexually transmitted chlamydial infection in the general population of Slovenia is substantial with estimated 1.6% infected females and 3.0% infected males among18 - 49 years old. Screening of women results in lower prevalence of chlamydial infection, pelvic inflammatory disease and ectopic pregnancy. The aim of the paper is to present and compare different recommendations for screening of chlamydial infection and to identify criteria most often used. Methods: Literature search in Medline database was conducted, using the terms "Chlamydia", "screening" and "recommendations". Also, websites of national public health institutions were searched. Results: Recommendations for screening of sexually transmitted chlamydial infection were published in four European countries and in Canada. In addition, recommendations were also prepared by three US public health institutions and later summarized by different medical associations. Most recommendations and guidelines for screening of sexually transmitted chlamydial infection recommend screening of all sexually active women up to 25 years old as well as sexually active women older than 25 with additional risk factors for chlamydial infection, for example, a new or several sexual partners in the last year. Some recommendations include also screening of men, for example, sexually active men under 25 years old or sexually active men with additional risk factors. The issue of optimal interval for screening remains unresolved. Most recommendations suggest screening once per year while some also suggest that screening can be more frequent according to the risk assessment. Conclusions: To reduce a substantial burden of chlamydial infection in Slovenia, public health appropriateness of introduction of screening will have to be considered. These results will help to prepare screening recommendations for Slovenia.
Keywords: Chlamydia trachomatis; diagnostika; infekcije; Slovenia; Slovenija; spolno prenosljive bolezni